„WIDZĘ BŁYSZCZĄCE TWE ŚLADY...”. ROMANTYCZNE PODRÓŻE STANISŁAWA MAKOWSKIEGO - Szargot, Maciej (Prace Polonistyczne, 2022)
The article discusses the works of Stanisław Makowski: Świat “Sonetów krymskich” Adama Mickiewicza, W szwajcarskich górach. Krajobrazy alpejskie Słowackiego and Okopy Świętej Trójcy. These monographs are informed by the researcher’s intention to travel in the footsteps of the poets (Mickiewicz, Słowacki, Krasiński), and they juxtapose the topographic realities with their literary mapping. Since the idea of such a trip taken by a literary scholar comes directly from the tradition of genetic research, the author of the article examines Makowski’s attitude to this methodology and to the principle of combining it with ergocentric research. He also investigates Makowski’s way of implementing and combining various goals: editorial goals, goals related to literary studies, and his intention to create a guidebook or a reportage about the places visited by the poets.